Optimizing Transfer Pricing in Indonesia: An exploring of Tax Minimization, Tunneling incentive, and Audit Committees - Pamungkas, Imang Dapit; Nehayati, Nela (Faculty of Economics, Universitas Sriwijaya, 2024)
Transfer pricing has become a crucial aspect, especially for natural resource companies in Indonesia, which includes monitoring tax compliance, mitigating tax dispute risks, and maintaining corporate reputation due to its complex and high-priced commodities. This research aims to test and analyze the direct influence of tax minimization strategy, tunnelling incentive, and bonus mechanism on transfer pricing decisions. Meanwhile, the indirect effect involves the audit committee as a moderating factor to explore their influence on transfer pricing practices. The data was derived from the annual reports of natural resource sector companies listed on the Indonesia Stock Exchange. A total of 185 companies used the purposive sampling method, resulting ina sample of 146 data analyzed using WarpPLS 8.0. According to the research results, tax minimization directly influences transfer pricing. In contrast, tunnelling incentives do not affect transfer pricing, and audit committees moderate the influence of bonus mechanisms on transfer pricing.